Safety Assessment of Cat’s Whiskers Flavonoid in Development Toxicity of Zebrafish Embryos - Das, Rajat; Maji, Himangshu Sekhar; Haldar, Pallab Kanti; Bala, Asis (Current Bioactive Compounds, 2025)
IntroductionThe pharmacological significance of 5-hydroxy-3,7,4'-trimethoxy flavone (5HTMF), a flavonoid isolated from Cleome gynandra L. (Capparidaceae), in mononuclear lymphocytes of patients with Rheumatoid Arthritis (RA) has been well-documented. In previous studies, the anti-inflammatory and anti-arthritis activity of CWF was reported.MethodsHowever, there is a lack of information on the toxicity of 5HTMF. This study aimed to assess the embryonic toxicity of 5HTMF on zebrafish embryos, using dexamethasone as a standard for liver toxicity. At 12 hours post fertilization (hpf), no significant toxicity from 5HTMF was observed on allantoic membrane development.ResultsBy 24 hpf, 20% of embryos showed minor changes in tail development at a 100 μM concentration of 5HTMF, while dexamethasone (10 μM) disrupted the allantoic membrane in 61.11% of embryos. In the liver toxicity assay, 5HTMF did not show any significant toxicity.ConclusionAt 48 hpf, dexamethasone exhibited substantial toxicity at a concentration of 10 μM. In conclusion, the findings suggest that 5HTMF may be a safe and non-toxic dietary supplement for treating chronic inflammatory conditions such as RA.
Keywords: streptavidin-peroxidase assay